2021
DOI: 10.1016/j.jamcollsurg.2020.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Deficit in US Surgical Training: The Trainee's Perspective

Abstract: BACKGROUND: Self-efficacy is the personal judgment of how well one can successfully complete a task. The goal of this study was to assess self-efficacy of PGY5 residents for common general surgery operations. We hypothesized there are deficits in self-efficacy of PGY5 residents, and self-efficacy of a given operation correlates with experience performing the operation without attending assistance (independently) and teaching the operation from start to finish. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…There have been increasing concerns regarding the disadvantages and limitations of the current educational process for general surgery residents; this is reflected in several articles [3][4][5][6] published in the medical literature that try to identify the current problems and offer solutions. We believe that this subject is worth exploring, and raised awareness of in this topic might be the way to successfully meet the needs of residents in training.…”
Section: Discussionmentioning
confidence: 99%
“…There have been increasing concerns regarding the disadvantages and limitations of the current educational process for general surgery residents; this is reflected in several articles [3][4][5][6] published in the medical literature that try to identify the current problems and offer solutions. We believe that this subject is worth exploring, and raised awareness of in this topic might be the way to successfully meet the needs of residents in training.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the methods previously described, self-efficacy was considered to be a binary construct; thus, only a score of 5 was considered indicative of self-efficacy. 2 The entrustment scale utilized in the PD survey matched that of the 2020 post-ABSITE survey as described in Kearse et al in 2021. 8 Program directors were queried about how frequently residents' preoperative assessments and operative plans were modified by the attending surgeon using the following scale: 1-always, 2frequently, 3-occasionally, 4-rarely, 5-never.…”
Section: Methodsmentioning
confidence: 99%
“…Previous literature has shown that graduating general surgery residents do not consider themselves to be self-efficacious at many commonly performed general surgery procedures. 2 Anderson et al conducted a survey associated with the American Board of Surgery In-Training Examination (ABSITE) in 2020 and identified a significant training deficit in general surgery residency programs, with 92.3% of graduating trainees feeling incapable of independently performing 1 or more of the 10 common core general surgery procedures included on the survey. 2 These operations included 4 laparoscopic procedures (laparoscopic appendectomy, cholecystectomy, right hemicolectomy, and diagnostic laparoscopy) and 6 open procedures (thyroidectomy, trauma exploratory laparotomy, trauma thoracotomy, wide local excision, breast biopsy, and inguinal hernia repair).…”
Section: Introductionmentioning
confidence: 99%
“…2 Moreover, we learned that the majority of the difference in patient outcomes between new and experienced surgeons is related to differences in the types of operations performed and the emergent state of presentation for many patients of the new surgeons. 3 To complement this work, health services research methods using a novel educational data source 4 have been used to demonstrate that, although 90% of graduating chiefs are rated as practice ready by supervising surgeons, results vary substantially across procedure types, and many graduating residents (>90%) report deficits in their preparation to practice just 6 months before graduation 5,6 This means that for the individual patient treated by an individual new surgeon, there may be room for improvement. Health services research tools, including matching to provide superior risk adjustment, a difference-in-difference study design to control for simultaneous changes to the nature of surgical practice across time, and collaboration across programs to collect data on trainee performance, provide a mechanism to measure the performance of educational paradigms.…”
Section: Leveraging the Health Services Research Toolbox For Surgical...mentioning
confidence: 99%